Parental contribution analysis in hybrids bred for vascular streak dieback (VSD) disease resistance in cocoa - P.A. Jayasree, J.S. Minimol, B. Suma, Mahiya Ummer (Journal of Plantation Crops, 2016)
Vascular streak die back (VSD) disease caused by Oncobasidium theobromae (now renamed as Ceratobasidium theobromae), is one of the major threats in cocoa growing countries, mainly becauseit cannot be controlled by any chemical application. In India, this disease outbreak took place during 1990 and it became an unmanageable problem of cocoa trees. Knowing the importance of resistant hybrids for controlling this disease, Kerala Agricultural University took up resistant breeding programme. It was a massive breeding programme which resulted in production of 5921 hybrid seedlings. After nursery screening of these hybrids by subjecting to heavy inoculation load for more than two years from March 1996 to June 1998, only 566 seedlings survived and they were field planted during June 1998. When relative efficiency of mother plants to transfer resistance to their progenies was estimated, it was seen that G VI 126 (Scavina 6) showed maximum recovery of 32.6 per cent after fifteen years of screening. Comparison of efficacy of male parents indicated that G VI 55 showed maximum recovery of resistant parents (168 nos.). During the entire period of investigation, 267 hybrids were found free from the disease. Out of this, only 51 recorded satisfactory yield levels. All these hybrids showed high value for selection differential (S) indicating maximum genetic gain.These hybrids can be used as mother plants for establishing polyclonal garden, as VSD disease resistance is highly heritable and polygenically controlled. The resistant hybrids identified (both high and low yield) can be utilized for further studies employing conventional and molecular breeding methods.